The inhibitory effect of adenosine on tumor adaptive immunity and intervention strategies - Longsheng Wang; Jie Zhang; Wenxin Zhang; Mingming Zheng; Hongjie Guo; Xiaohui Pan; Wen Li; Bo Yang; Ling Ding (Elsevier, 2024)
Adenosine (Ado) is significantly elevated in the tumor microenvironment (TME) compared to normal tissues. It binds to adenosine receptors (AdoRs), suppressing tumor antigen presentation and immune cell activation, thereby inhibiting tumor adaptive immunity. Ado downregulates major histocompatibility complex II (MHC II) and co-stimulatory factors on dendritic cells (DCs) and macrophages, inhibiting antigen presentation. It suppresses anti-tumor cytokine secretion and T cell activation by disrupting T cell receptor (TCR) binding and signal transduction. Ado also inhibits chemokine secretion and KCa3.1 channel activity, impeding effector T cell trafficking and infiltration into the tumor site. Furthermore, Ado diminishes T cell cytotoxicity against tumor cells by promoting immune-suppressive cytokine secretion, upregulating immune checkpoint proteins, and enhancing immune-suppressive cell activity. Reducing Ado production in the TME can significantly enhance anti-tumor immune responses and improve the efficacy of other immunotherapies. Preclinical and clinical development of inhibitors targeting Ado generation or AdoRs is underway. Therefore, this article will summarize and analyze the inhibitory effects and molecular mechanisms of Ado on tumor adaptive immunity, as well as provide an overview of the latest advancements in targeting Ado pathways in anti-tumor immune responses.